2010
DOI: 10.1007/s13149-010-0101-9
|View full text |Cite
|
Sign up to set email alerts
|

Prévalence de l’obésité de l’enfant et de l’adolescent en milieu scolaire à Dakar

Abstract: Obesity is currently viewed as a serious worldwide public health issue. In this survey, we aim to determine its prevalence among schoolchildren and teenagers in Dakar. The sample of our survey consisted of 2,356 students aged 11-17, including 1,110 boys and 1,246 girls. For each of them, we have calculated their body mass index. Based on the higher value of the norm of that index, referred to the 97th percentile of Rolland-Cachera MF's curves, we have identified obese students according to their age and sex. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 11 publications
0
6
0
1
Order By: Relevance
“…En Tunisie, 18.9% des adolescents sont en surpoids et 4% sont obèses [16]. En 2011, une étude menée au Sénégal auprès des adolescents âgés de 11 à 17 sans au sein des établissements publics et privés de Dakar, indiquait une prévalence de 9,3% d’obésité [17]. Très peu d’études ont été consacrées au surpoids et à l’obésité dans notre milieu; ainsi cette étude avait pour objectif de déterminer la prévalence de ces deux pathologies chez les adolescents en milieu scolaire dans la ville de Lubumbashi en République Démocratique du Congo (RDC).…”
Section: Introductionunclassified
“…En Tunisie, 18.9% des adolescents sont en surpoids et 4% sont obèses [16]. En 2011, une étude menée au Sénégal auprès des adolescents âgés de 11 à 17 sans au sein des établissements publics et privés de Dakar, indiquait une prévalence de 9,3% d’obésité [17]. Très peu d’études ont été consacrées au surpoids et à l’obésité dans notre milieu; ainsi cette étude avait pour objectif de déterminer la prévalence de ces deux pathologies chez les adolescents en milieu scolaire dans la ville de Lubumbashi en République Démocratique du Congo (RDC).…”
Section: Introductionunclassified
“…The inter-rater agreement at the full-text screening (Kappa statistic = 0.75, p < 0.01) and data extraction (Kappa statistic = 0.87, p < 0.01) stages shows there was a moderate to a substantial level of agreement respectively. Of the 31 articles excluded at the full-text screening stage, 17 did not report any of this study’s outcomes of interest [ 3 , 33 48 ], 7 were review studies [ 20 , 49 54 ], 4 were published in French though their titles and abstracts were in English [ 55 58 ], 2 reported evidence outside this study’s population age range [ 59 , 60 ], and 1 study was not conducted in of SSA [ 61 ].
Fig.
…”
Section: Resultsmentioning
confidence: 99%
“…This could be explained by changes in children's eating habits through the consumption of fatty and sugary foods, but also the lack of physical activity. Some studies in West Africa [11,16,22] and elsewhere [1,4,5,15,[23][24][25] have reported various frequencies regarding obesity and overweight. In Europe, a study in seven countries among primary school children revealed proportions of 15.6% overweightness and 4.9% obesity [7].…”
Section: Discussionmentioning
confidence: 99%
“…These studies have focused on different age groups ranging from 5 to 17 years and used different ways of measuring obesity or overweight. Thus, the prevalence of obesity and overweight ranged between 0.8-10.3% and 1.5 to 17.0%, respectively [10][11][12][13][14][15][16][17][18].…”
Section: Introductionmentioning
confidence: 99%